A Method for SWIM-Compliant Human-in-the-Loop Simulation of Airport Air Traffic Management. (27th July 2016) - Gräupl, Thomas; Mayr, Martin; Rokitansky, Carl-Herbert
Abstract : System Wide Information Management (SWIM), as envisioned by the Single European Sky Air Traffic Management Research (SESAR) program, is the application of service oriented architectures to the air traffic management domain. Service oriented architectures are widely deployed in business and finance but usually tied to one specific technological implementation. SWIM goes one step further by defining only the semantic layer of the application integration and leaving the implementation of the communication layer open to the implementer. The shift from legacy communication patterns to SWIM is fundamental for the expected evolution of air traffic management in the next decades. However, the air traffic management simulators currently in use do not reflect this yet. SWIM compliance is defined by semantic compatibility to the Air Traffic Management Information Reference Model (AIRM) and a SWIM service may implement one or more communication profiles, which specify a communication layer implementation. This work proposes a SWIM-compliant communication profile suitable to integrate SWIM-compliant tools into human-in-the-loop simulations for air traffic management research. We achieve this objective by implementing a SWIM communication profile using XML-based multicast messaging and extending the message format to support distributed human-in-the-loop simulations. We demonstrate our method by the evaluation of Hamburg Airport operations.